2014
DOI: 10.1158/1078-0432.ccr-13-2287
|View full text |Cite
|
Sign up to set email alerts
|

Germline and Somatic Mutations in Homologous Recombination Genes Predict Platinum Response and Survival in Ovarian, Fallopian Tube, and Peritoneal Carcinomas

Abstract: Purpose Hallmarks of germline BRCA1/2-associated ovarian carcinomas include chemosensitivity and improved survival. The therapeutic impact of somatic BRCA1/2 mutations and mutations in other homologous recombination (HR) DNA repair genes is uncertain. Experimental Design Using targeted capture and massively parallel genomic sequencing, we assessed 390 ovarian carcinomas for germline and somatic loss-of-function mutations in 30 genes, including BRCA1, BRCA2, and 11 other genes in the HR pathway. Results 31%… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
807
3
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 872 publications
(872 citation statements)
references
References 35 publications
44
807
3
18
Order By: Relevance
“…3,4,[12][13][14][15][16][17][18][19] Only one PARPi has been FDA approved for the treatment of ovarian cancer, olaparib, and this is only in the setting of BRCA mutation and at least three prior lines of chemotherapy. Our findings further support the work of Pennington et al, 21 suggesting that a broader population of women with ovarian cancer may benefit from PARPi therapy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…3,4,[12][13][14][15][16][17][18][19] Only one PARPi has been FDA approved for the treatment of ovarian cancer, olaparib, and this is only in the setting of BRCA mutation and at least three prior lines of chemotherapy. Our findings further support the work of Pennington et al, 21 suggesting that a broader population of women with ovarian cancer may benefit from PARPi therapy.…”
Section: Discussionsupporting
confidence: 90%
“…20 In addition, we confirmed the prevalence of mutations in homologous recombination pathway genes across tumor histotypes, ranging from 25 to 45% of cases. 21 However, it is possible that this number is an underestimate of the actual prevalence, owing to the fact that our targeted panel was not entirely inclusive of all genes involved in homologous recombination, 21 as well as the fact that we were conservative by including only loss-of-function mutations or missense mutations that had been reported previously. In addition, although we did not evaluate epigenetic mechanisms of inactivating homologous recombination genes, such as promoter methylation, it has been shown that patients with epigenetically silenced BRCA1 have similar survival to patients with wild-type BRCA1/2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a mutation of PALB2 has been described to sensitive pancreatic cancer to mitomycin C treatment by disrupting BRCA1 and BRCA2 interactions (4). Similarly, ATM mutations are predicted to result in increased sensitivity to platinum chemotherapy (6,67). However, a recent preclinical study in gynecologic cancer cell lines found that ATM inhibition enhanced the response to ionizing radiation, but did not enhance the in vitro killing of the cells by platinum drugs (68).…”
Section: Platinum Drugsmentioning
confidence: 99%
“…4−6 Half of all high-grade serous ovarian carcinomas are estimated to have homologous recombination defi ciency, with about 15% of carcinomas harbouring a germline BRCA mutation, 6% a somatic BRCA mutation, and 20% a mutation in, or epigenetic silencing of, another homologous recombination gene. 7,8 Even without an identifi able mutation in BRCA or other known homologous recombination gene, many high-grade serous ovarian carcinomas show BRCA mutant-like genomic signatures, 6,9 which could serve as a downstream marker of homologous recombination defi ciency.…”
Section: Introductionmentioning
confidence: 99%